Highland Plateau Amhara of Ethiopia - Messing, Simon D.; Bender, M. Lionel (Human Relations Area Files, 1985)
SCSU Faculty Scholar Award
Keywords: Amhara (African people); Amharic language; Glossaries; vocabularies; etc; award_winner; dept.ant; faculty_collection

A Holistic Reader in Applied Anthropology: The Target of Health in Ethiopia, - Messing, Simon D. (MSS Information Corp, 1973)
Keywords: Ethiopia; Medical anthropology; Applied anthropology; Ethnology; dept.ant; faculty_collection

Encyclopedia of Anthropology - Hunter, David E.; Whitten, Phillip (Harper & Row, 1976)
Keywords: Anthropology; Dictionaries; dept.ant; faculty_collection

The study of anthropology - Hunter, David E.; Whitten, Phillip (Harper & Row, 1976)
Keywords: Anthropology; dept.ant; faculty_collection

Some Human Factors Problems and Possibilities in Developing Ethiopia - Messing, S.D. (Human Factors: The Journal of Human Factors and Ergonomics Society, 1968)
Both negative and positive cultural factors affect innovative efforts in developing countries. In the case of Ethiopia, negative factors include a low esteem for craftsmanship. Even where modern education is making inroads on some negative factors, as in the towns, feudalistic attitudes toward labor and the preference for unskilled labor on the assumption that it is more economical, act to continue functionally inefficient attitudes. In contrast, positive factors exist in traditions of mutual aid, now spreading from South Ethiopian cultures northward. An excellent model for mutual aid may be found in the practices of the migrant weavers' association of the Gurage and some neighboring tribes. Ethiopia provides an interesting area for the study of human factors in developing countries since it has not passed through a colonial period. Various stages of development can be traced comparatively free of outside influences. © 1968, Human Factors and Ergonomics Society. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.ant

Ethiopian revolution [3] - Messing, S.D. (Science, 1975)
0 citations (Crossref) [2023-10-31]
Keywords: dept.ant

Social problems related to the development of health in Ethiopia - Messing, S.D. (Social Science and Medicine, 1970)
The relationship between the development of public health programs and "social problems" is of increasing concern to students of social and cultural problems. Health is obviously related to the availability of good nutrition, essential in building resistance against contagious diseases that form the bulk of preventable health problems in underdeveloped countries. Good nutrition, in turn, is dependent upon availability of agricultural products, basic income to buy them, and education to utilize them properly. This article attempts to trace, briefly, some of the etiology of these interrelated problems in a country in which traditional values have not been distorted by a foreign-established colonial period, and which has experienced only superficial change in modern times. This makes it possible to view relationships more clearly than in other underdeveloped countries where they may exist in more complex forms. © 1970.
3 citations (Crossref) [2023-10-31]
Keywords: Agriculture; Attitude to Health; Circumcision; Ethiopia; Folklore; Government; Health Planning; Human; Nutrition; Public Health; Rural Health; Social Change; Socioeconomic Factors; Taboo; Urbanization; agriculture; article; attitude; circumcision; cultural anthropology; dept.ant; ethnic group; government; health; health care planning; human; nutrition; public health; socioeconomics; sociology; urbanization

Two tactics for ethnic survival-Eskimo ℰ Indian - Dryfoos, Robert J. (Trans-action, 1970)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1970G379300006, dryfoosTwoTacticsEthnic1970, lens.org/039-174-037-005-733, pop00209 tex.type: [object Object] tex.unique-id: [object Object]
Keywords: dept.ant

Discounting health: The issue of subsistence and care in an undeveloped country - Messing, Simon D (Social Science & Medicine, 1973)
The concept "discounting health" is proposed as a heuristic model for analysis of differing perceptions concerning "cost-benefit", as these relate to systems of health care. This procedure became necessary during analysis of data gathered in rural Ethiopia to measure the effectiveness of new Health Centers. Ethnological research accompanying the quantitative study of health attitudes found that "subsistence anxiety" dominated all other concerns of the majority in the rural areas. The landless peasant sharecropper and his divorced wife represent the most prevalent social problem in Ethiopia. Holistic solutions should include some form of social security and safe wells, so that the population can stop "discounting health". © 1973.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-649-364-861-026 tex.type: [object Object]
Keywords: Absenteeism; Anxiety; Attitude to Health; Child; Community Health Services; Delivery of Health Care; Economics; Epidemiology; Ethiopia; Ethnic Groups; Health Education; Human; Income; Legislation; Medical; Life Style; Models; Theoretical; Preventive Health Services; Questionnaires; Rural Health; Sanitation; anxiety; dept.ant; developing country; finance; health center; health service; methodology; model; primary health care; public health service

The archaeological implications of water-cached hyena kills - Selvaggio, M.M. (Current Anthropology, 1998)
11 citations (Crossref) [2023-10-31]
Keywords: dept.ant

Concerning the three stage model of carcass processing at FLKZinjanthropus: A reply to Capaldo - Selvaggio, Marie M (Journal of Human Evolution, 1998)
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/004-801-145-000-921 tex.type: [object Object]
Keywords: Animals; Anthropology; Carnivora; Feeding Behavior; Fossils; Hominidae; Humans; Models; Biological; animal; anthropology; biological model; dept.ant; feeding behavior; fossil; hominid; human; note; peer-reviewed; ⛔ No DOI found

Evidence for a three-stage sequence of hominid and carnivore involvement with long bones at FLKZinjanthropus, olduvai gorge, tanzania - Selvaggio, Marie M (Journal of Archaeological Science, 1998)
The order in which hominids and carnivores had access to Plio-Pleistocene bone assemblages has defied interpretation despite attempts to decipher their sequence from element frequencies or by comparing ancient butchery marks with modern ones. Data from two simulations in which experimental stone-tool butchery of long bones occurred after carcasses were defleshed by large free-ranging East African carnivores are here compared to data from the FLK Zinjanthropus bone assemblage from Olduvai Gorge, Tanzania. One experimental sample simulated two stages of tissue removal; defleshing of long bones by carnivores, followed by tool-assisted flesh-scrap removal and marrow extraction. A second simulated three stages of tissue removal; the first two stages the same as the first sample, plus a third stage in which bone-crunching carnivores ravaged the remains. Carnivore ravaging is demonstrated to result in additional tooth marks on epiphyseal fragments, but does not significantly alter the incidence of defleshing tooth marks or butchery marks on midshafts. The Zinjanthropus sample is similar to the three-stage simulation in its proportion of epiphyseal relative to midshaft fragments, and for the incidence of midshafts bearing tooth marks and butchery marks. © 1998 Academic Press Limited.
86 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-024-831-197-63X tex.type: [object Object]
Keywords: Butchery Marks; Carnivore Tooth Marks; Experimental Archaeology; Pleistocene; Pliocene; Scavenging; Site Formation; Tanzania; Taphonomy; archaeology; bone assemblage; dept.ant; taphonomy